Alkaline phosphatase activity and its relationship to inorganic phosphorus in the transition zone of the North-western African upwelling system - Sebastián, Marta; Arístegui, Javier; Montero, María F.; Escánez, José; Niell, F. Xavier (Progress in Oceanography, 2004)
20 pages, 10 figures, 2 tables The enzymatic activity of alkaline phosphatase (APA) was studied in the transition zone between the African upwelling system and the open ocean waters of the Canary Islands region. This region is recurrently dominated by the presence of upwelling filaments that may transport nutrient-enriched waters out into the open ocean before nutrients become exhausted by plankton. Turnover rates by APA were generally low in the whole region, but detectable in all the measurements carried out. On average, turnover rates were higher in the upwelling stations, and APA in those waters seemed to be mainly generated by heterotrophic bacteria to supply easily assimilable organic C. APA outside the upwelling area showed an inverse hyperbolic relationship with increasing phosphate, suggesting the presence of both constitutive and Pi-inducible APA. In these offshore waters, a threshold of 0.1 μM of phosphate could be defined for the regulatory function of Pi on APA. Thus, APA in nutrient-poor waters seemed to be induced to compensate for Pi-deficiency. Turnover rates in the filaments showed basal (probably constitutive) levels, whereas they increased in the surrounding waters, where phosphate concentration presumably did not satisfy plankton P-demands. The fertilising effect of the filaments and associated cyclonic eddies extended to at least 175 km offshore, where basal alkaline phosphatase activities were still found. The magnitude of this effect depends probably on the intensity of upwelling events and the degree of recirculation of filament water back to the coastal jet Peer reviewed